1993
DOI: 10.1172/jci116782
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of direct estrogenic regulation of human corticotropin-releasing hormone gene expression. Potential implications for the sexual dimophism of the stress response and immune/inflammatory reaction.

Abstract: Corticotropin-releasing hormone (CRH) plays major roles in coordination of the stress response and regulation of the immune/inflammatory reaction, two important functions associated with sexual dimorphism. Two overlapping segments of the 5' flanking region of the human (h) CRH gene, the proximal 0.9 kb (containing two perfect half-palindromic estrogenresponsive elements IEREsI) and the 2.4 kb (including the former and containing two additional perfect half-palindromic EREs), were examined for their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
208
3
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(222 citation statements)
references
References 58 publications
6
208
3
5
Order By: Relevance
“…Evidence suggests that, within the central nervous system, estrogen alters the expression of specific genes related to pain signaling to increase perception of peripheral nociceptive stimuli. [101][102][103] These estrogen-dependent alterations in gene expression increase neuronal excitability by promoting synaptic plasticity leading to increased visceral sensitivity in females, especially during periods of high cycling estrogen. 104 Another estrogenmediated mechanism that could drive visceral hypersensitivity is via the induction of ”-opioid receptor internalization within the medial preoptic nucleus and the posterodorsal medial amygdala.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…Evidence suggests that, within the central nervous system, estrogen alters the expression of specific genes related to pain signaling to increase perception of peripheral nociceptive stimuli. [101][102][103] These estrogen-dependent alterations in gene expression increase neuronal excitability by promoting synaptic plasticity leading to increased visceral sensitivity in females, especially during periods of high cycling estrogen. 104 Another estrogenmediated mechanism that could drive visceral hypersensitivity is via the induction of ”-opioid receptor internalization within the medial preoptic nucleus and the posterodorsal medial amygdala.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…In general, estrogen increases the immune response (Grossman, 1984) and androgens inhibit it (Spinedi et al, 1992) such that females have more pronounced responses than males to immune activation. Sex steroids also influence HPA axis activity, since estrogen positively (Vamvakopoulos and Chrousos, 1993) and androgen negatively (Bingaman et al, 1994) modulate corticotrophin releasing hormone (CRH) production such that females exhibit higher plasma corticosterone (CORT) levels compared to males. Studies examining adrenal function following endotoxin (LPS) administration in mice, have found that female plasma CORT levels are significantly higher than male levels regardless of the post-administration time point examined (Spinedi et al, 2004).…”
Section: Cytokine-sex Steroid-immune System Interactionsmentioning
confidence: 99%
“…28,29 There are five perfect half-palindromic estrogenresponsive elements in the human CRF-promoter region, which may confer direct estrogenic stimulation on CRF gene expression. 28,65 Differential effects have been described in vitro on gene expression by the two receptor subtypes ESR1 and 2. 66 ESR1 mRNA expression dominates in the human hypothalamus while ESR2 mRNA and protein were lower in this brain area.…”
Section: Sex Hormones Receptor Imbalancementioning
confidence: 99%